Pelaksanaan Pendaftaran Tanah Sistematis Lengkap Di Desa Brabowan Kecamatan Sambong Kabupaten Blora - Muhamad Mukti Pranoto; Edi Pranoto; Muhammad Soleh (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
This study aims to determine the Implementation of Complete Systematic Land Registration in Brabowan Village, Jiken District, Blora District, especially the implementation of land surveying by researchers, with the formulation of the problem posed is How is the implementation of land registration through Complete Systematic Land Registration (PTSL) in Brawoban Village, Sambong District Blora Regency and what factors or factors become obstacles or obstacles in the implementation of Complete Systematic Land Registration (PTSL) in Brawoban Village, Sambong District, Blora Regency. This research is included in normative juridical law research. The legal materials used are primary and secondary legal materials collected through direct observation by researchers and supported by literature. The analysis was carried out using qualitative methods. The approach used is descriptive analysis, namely research conducted in the field and then presented and compared with the applicable laws and regulations.